Snow Cover seasonality in Kyrgyzstan 2001-2021 observed by the Terra MODIS snow product - Tomaszewska, Monika; Henebry, Geoffrey
Using two decades of MODIS snow-cover data, we investigated trends in four snow seasonality metrics: First Date of Snow (FDoS); Last Date of Snow (LDoS); Duration of the Snow Season (DoSS); and Snow-Covered Days (SCD) across Kyrgyzstan. In our nonparametric approach, we analyzed trends within elevation ranges at two administrative levels: oblast and rayon. We found notable trends to earlier FDoS below 3000 m and more SCD between 1500-3500 m in western KG. We also found the notable trends towards earlier LDoS at both oblast and rayon levels. This analysis revealed more area (107-130%) trending to earlier FDoS than earlier LDoS, highlighting a counterintuitive finding: longer snow seasons starting earlier at lower elevations.
Keywords: Seminaria IGiK